Impact of pre‐ and post‐pollination barriers on pollen transfer and reproductive isolation among three sympatric Pedicularis (Orobanchaceae) species. (21st May 2018) - Liang, H.; Ren, Z.‐X.; Tao, Z.‐B.; Zhao, Y.‐H.; Bernhardt, P.; Li, D.‐Z.; Wang, H.
Abstract: Pedicularis is the largest genus in the Orobanchaceae (>300) with many species co‐occurring and co‐blooming in subalpine to alpine meadows in the Himalayas. Although it is well known that different Pedicularis species place pollen on different parts of the same bumblebee's body, thus reducing interspecific pollen transfer, it is not known whether post‐pollination components also contribute to reproductive isolation (RI). In this study, we quantified the individual strengths and absolute contributions of six pre‐ and post‐pollination components of RI between three sympatric species in two pairs; Pedicularis gruina  ×  Pedicularis tenuisecta ( gru  ×  ten ) and Pedicularis comptoniifolia  ×  Pedicularis tenuisecta ( com  ×  ten ). All three Pedicularis species shared the same Bombus species. Individual foragers showed a high, but incomplete, floral constancy for each species. Therefore, pre‐pollination barriers were potentially 'leaky' as Bombus species showed a low but consistent frequency of interspecific visitation. The RI strength of pre‐pollination was lower in com  ×  ten than in gru  ×  ten . In contrast, post‐pollination barriers completely blocked gene flow between both sets of species pairs. Two post‐pollination recognition sites were identified. Late acting rejection of interspecific pollen tube growth occurred in com ♀ ×  ten ♂, while seeds produced in bi‐directional crosses of gru  ×  ten failed to germinate. We propose that, although floral isolation based on pollen placement on pollinators in the genus Pedicularis is crucial to avoid interspecific pollen transfer, the importance of this mode of interspecific isolation may be exaggerated. Post‐pollination barriers may play even larger roles for currently established populations of co‐blooming and sympatric species in this huge genus in the Himalayas.